Market abuse and insider dealing - Rider, Barry Alexander K.; Alexander Kern,Linklater Lisa (London Butterworths, 2002)
Butterworths Compliance Series: Market Abuse and Insider Dealing forms part of a series of guidebooks published by Butterworths addressing legal and compliance obligation arising mainly under the Financial Services Authority. The book examines the new offence of market abuse, as well as the crime of insider dealing and a number of other fraud- related offences. It focuses on the responsibilities of those engaged in compliance, as well as those who fall within the scope of the prohibitions.
Includes Index
ocf. 26/02/19
Loans
Keywords: Insider trading in securities; Market Abuse